1981
DOI: 10.1111/j.1570-7458.1981.tb03044.x
|View full text |Cite
|
Sign up to set email alerts
|

THE GENETICS OF THE “BIOTYPES” OF THE RICE BROWN PLANTHOPPER, NILAPARVATA LUGENS

Abstract: As the resistance of rice varieties to the brown planthopper is based on major genes it has been widely assumed that there is a gene for gene correspondence between resistance on the part of the plant and virulence on the part of the hopper. However, the mode of inheritance and response of the biotypes to selection. together with the previously reported wide variation within each “biotype” and large overlap between them in virulence, is all consistent with polygenic determination of virulence. RÉSUMÉ LA GÉNÉTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…In those studies, progenies in virulent/avirulent hybrids did not show typical segregation ratios for the virulence to resistant rice varieties. It has been suggested that the cause of indefinite segregations in the genetic analyses of BPH virulence is due to the polygenic nature of the physiological traits or the genetic heterogeneity of parental 'biotype' populations [15,16]. Our different conclusion regarding the genetics of BPH virulence from that of previous studies seems to largely depend on the purity of the biological materials and accurate evaluation of virulence.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In those studies, progenies in virulent/avirulent hybrids did not show typical segregation ratios for the virulence to resistant rice varieties. It has been suggested that the cause of indefinite segregations in the genetic analyses of BPH virulence is due to the polygenic nature of the physiological traits or the genetic heterogeneity of parental 'biotype' populations [15,16]. Our different conclusion regarding the genetics of BPH virulence from that of previous studies seems to largely depend on the purity of the biological materials and accurate evaluation of virulence.…”
Section: Discussionmentioning
confidence: 76%
“…Several genetic analyses of BPH 'biotypes' have been conducted, and most of the studies have suggested polygenic control of BPH virulence to rice resistance genes [15][16][17]. The recessive nature of the virulence to Bph1 was also reported [11,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for a long time that rice resistance to BPH could be overcome by a new ''biotype'' of BPH, which is a virulent strain of the insect with the ability to survive on and damage the previously resistant varieties (39). Although the precise nature of BPH biotype and rice resistance is not clear, their interaction is analogous to ''gene-for-gene'' interaction of the plant/pathogen systems (39,40). Identification of Bph14 in this study makes it clear that a CC-NB-LRR gene mediates such a specific genefor-gene resistance in rice to BPH.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the BPH populations retain polygenic flexibility to modify their biotype compositions to overcome the sucking blockage by Bph1 and bph2 (den Hollander and Pathak 1981;Roderick 1994;Tanaka 1999). Accordingly, IR26 and IR42 showed only temporary vertical (resistance gene and biotype specific) resistance until a BPH population adjusts their biotype makeup so as to feed on those resistant varieties.…”
Section: Tentative Vertical Resistance In Ir26 and Ir42mentioning
confidence: 97%